284 Opiate Administration to Preterm Infants - A Risk Factor for Necrotising Enterocolitis?. (October 2012) - Krishnamurthy, M; How, M; Wilson, E; Cheng, W; Tan, K
Abstract : Background and Aims: Opiates like morphine and fentanyl are commonly used for sedation in the NICU. There are reports implicating early opiate exposure as a risk factor for NEC in preterm infants. We aimed to investigate if exposure to opiates in the first week of life was a risk factor for subsequent NEC in preterm infants in our NICU. Methods: Cases of NEC (Bell Stage ≥2) in infants < 32 weeks gestation age (GA) over a 3-year period (Jan 2008-Dec 2010) were identified from the NICU database. A case-control study was performed by pairing each infant with NEC to a random control, matched for year of birth, GA (±1 week) and birthweight (BW ± 20%). Total exposure to opiates (morphine and fentanyl) between days 1 and 7 was tabulated from medical records and the database. Two-tailed Fisher's exact test was used to calculate the risk. Results: 27 infants with definite NEC were identified with mean GA (±SD) of 27.2(±2.1) weeks and BW of 998 (±348) g. 54 controls were matched with mean (±SD) GA 0f 27.3 (±2.2) weeks and BW of 972(±346) g. Exposure to opiates was not different between NEC and controls ( P = 0.63; Odds Ratio (95% CI) of 0.73 (0.28–1.91). Median (range) daily opiate over the first week in NEC infants (morphine dose equivalent) was 14.3 (0–259) µg/kg/day or approx. 0.6 (0–11) µg/kg/hour. Conclusions: Early opiate exposure did not appear to be a significant risk factor for NEC in our population.